Insights into Biological and Ecological Features of Four Rare and Endemic Plants from the Northern Tian Shan (Kazakhstan) - Gulbanu Sadyrova; Aisha Taskuzhina; Alexandr Pozharskiy; Kuralai Orazbekova; Kirill Yanin; Nazym Kerimbek; Saule Zhamilova; Gulzhanat Kamiyeva; Ainur Tanybaeva; Dilyara Gritsenko (Plants)
This study presents an integrative investigation of four rare and threatened plant species—Taraxacum kok-saghyz L.E. Rodin, Astragalus rubtzovii Boriss., Schmalhausenia nidulans (Regel) Petr., and Rheum wittrockii Lundstr.—native to the Ile Alatau and Ketmen ridges of the Northern Tian Shan in Kazakhstan. Combining chloroplast genome sequencing, geobotanical surveys, and anatomical and population structure analyses, we aimed to assess the ecological adaptation, genetic distinctiveness, and conservation status of these species. Field surveys revealed that population structures varied across species, with T. kok-saghyz and S. nidulans dominated by mature vegetative and generative individuals, while A. rubtzovii and R. wittrockii exhibited stable age spectra marked by reproductive maturity and ongoing recruitment. Chloroplast genome assemblies revealed characteristic patterns of plastid evolution, including structural conservation in S. nidulans and R. wittrockii, and a reduced inverted repeat region in A. rubtzovii, consistent with its placement in the IR-lacking clade of Fabaceae. Morphological and anatomical traits reflected habitat-specific adaptations such as tomentose surfaces, thickened epidermis, and efficient vascular systems. Despite these adaptations, anthropogenic pressures including overgrazing and habitat degradation pose significant risks to population viability. Our findings underscore the need for targeted conservation measures, continuous monitoring, and habitat management to ensure the long-term survival of these ecologically and genetically valuable endemic species.